Intra-puparial development of Lucilia eximia (Diptera, Calliphoridae) (2017)
ABSTRACT: There are few studies about the intra-puparial development in Diptera, nonetheless its importance has been increased because several dipteran species are of forensic interest. Studies on the life cycles of flies often disregard the changes that occur inside the pupae. The objectives of this research were to analyze the intra-puparial development of Lucilia eximia, and to describe chronological and morphological changes that occur during this stage. Around 1.600 specimens were laboratory-reared. The pre-pupae were identified by the reduction of their size and change in coloration, and 10 individuals were sampled every three hours (n=1.000) until adult emergence. The specimens were fixed in 96% alcohol, subsequently immersed in Canoy solution for 24 hours and in formic acid (5%) for 48 hours, to facilitate dissection and analysis of the morphological changes of the individuals. Four stages of the intra-pupal development of L. eximia were observed: 1) Larva-pupa apolysis, which lasted 23 ± 1.08 h; 2) Cryptocephalic pupa, 5 ± 0.53 h; 3) Phanerocephalic pupa, 92 ± 1.94 h; and 4) Pharate adult: Transparents eyes, 125 ± 2.15 h; Yellow eyes, 23 ± 0.89 h; Pink eyes, 14 ± 0.73 h; and Red eyes, 20 ± 0.60 h. The pharate adult is completely formed after 296 hours and the emergence of the adult occurred after 302 ± 3.81 h. In addition, there were included the stage of pre-pupa, pupariation and the beginning of the adult stage, Imago and adult emergence. Each stage is described and compared with those described for Chrysomya albiceps (Calliphoridae).